STRATEGY OF MODERNIZATION OF POLITICAL-ADMINISTRATIVE INSTITUTIONS OF GOVERNANCE - Божко, П. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The strategy of modernization is the result of a rather complex process of interaction between the goals and interests of the ruling political elite, its capabilities and limitations in the creation of new political-administrative institutions that can be conductors of direct and reverse signals of interaction between society and government. For the successful implementation of the developed strategy of modernization, it is necessary to use the political-administrative mechanism, which includes exogenous and endogenous elements. The task of political governance is to determine the priorities and strategies of social development of the state, as well as the processing and translation of social values and expectations into a clear plan of action. Modernization is, first of all, the achievement of the competitiveness of institutions through their changes. For such changes at the first stage it is necessary to include the basic rules and regulations, the formation of which means the development of the political environment. That is why modernization must be viewed from an instrumental point of view: as a condition for the implementation of the strategic plans of political power. In this sense, the modernization of public administration is a political project. This approach allows us to see administrative changes within the political context, that is, to consider them as a process that occurs under the influence and during the clash of interests and interaction between different groups and individuals. Modernization of political-administrative governance in the direction of effective state formation is directly related to the improvement of the political system, efficient implementation of administrative reforms, rationalization of political-administrative interaction, optimization of the system of local self-government. It is important to determine the optimal balance between the goals of achieving economic efficiency in market conditions and the social orientation of the system of public administration in general. Characteristic of the modernization process is the structural and substantive transformation of the political system aimed at the formation of the political structure of social action.